Makna Motivasi pada Lirik Lagu “Diri” Karya Tulus - Viola Rezkhika Aulia Putri Kurnia Viola; Alex Sobur (UNISBA Press, 2023)
Abstract. This research is motivated by the many suicide attempts in 2020, which states that many people do not love themselves. Therefore, Tulus released his latest album entitled